1999
DOI: 10.1046/j.1365-2923.1999.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Objectives for the undergraduate teaching of psychiatry: survey of doctors and students

Abstract: These results confirm the importance of teaching psychiatry with an emphasis on problems encountered in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Their views support the results of a recent survey of 1593 doctors and 227 medical students in Geneva looking at the relative importance of psychiatric topics in undergraduate teaching, which found that learning about the doctorpatient relationship was considered the most important (Goerg et al, 1999).…”
Section: Yakeley Et Al Who Wants To Do Psychiatry? Original Paperssupporting
confidence: 75%
“…Their views support the results of a recent survey of 1593 doctors and 227 medical students in Geneva looking at the relative importance of psychiatric topics in undergraduate teaching, which found that learning about the doctorpatient relationship was considered the most important (Goerg et al, 1999).…”
Section: Yakeley Et Al Who Wants To Do Psychiatry? Original Paperssupporting
confidence: 75%
“…Female students almost regularly assess psychosocial disciplines more positively than their male colleagues (Alexander & Eagles 1990;Fabrega et al 1994). Relationalemotional aspects tend to be of greater importance to female doctors, which is probably a reflection of the specific role that women still play within our society (Goerg et al 1999). Female students of the traditional curriculum showed ATP-scores comparable to all students of the PBL curriculum irrespective of gender.…”
Section: Discussionmentioning
confidence: 94%
“…A number of curricula in psychiatry have been suggested, 5–8 but they have been defined by experts with little reference to the needs of non‐specialists for psychiatry competencies. Non‐specialists have been asked to rate the importance of psychiatric topics in some studies, 9–11 but the methods relied upon definitions of the original topics by psychiatrists, which may have adversely dominated the range of issues.…”
Section: Introductionmentioning
confidence: 99%